تأثير إدخال بيانات الحرارة في مراحل مشروعات المباني على سمك العازل الحراري للجدران والأ سطح (Journal of Building and Road Research, 2021)
This research draws the attention of structural designers and architects to the importance of employing the environmental data in all the construction stages of buildings. The research focuses on the introduction of the solar radiationvalues that are received by the buildings during daytime for selecting building construction material of suitable thermal specifcations, as well as design of thermal insulation thickness for the building walls and roof.The research assumes the walls and roof are the media of heat exchange between the internal space and the climate, excluding the ﬂoors. The main heat transfer equation is used for the production of values of thermal conductivityat the level of the building, not the region. The research minded the fnancial situation of the owners and assumes three thermal levels for a building in the study area (Khartoum State).
Keywords: بيانات الحرارة; مشروعات المباني; سمك العازل الحراري